Design feasibility of long-span composite bridge with corrugated steel webs. Issue 7 (4th July 2019) - Liu, Duo; Zhao, Xingbao; Zhang, Jiandong; Deng, Wenqin
Abstract : A partial cable-stayed composite girder bridge with prestressed concrete flanges and corrugated steel webs (CSWs) is a beneficial new type of bridge structure that provides lower structural weight, reduced structural depth, increased span and lower seismic response. The structural responses and cost of four bridge types (a partial stayed-cable composite bridge with CSWs, a partial stayed-cable concrete bridge, a cable-stayed composite bridge with CSWs and a continuous rigid-frame composite bridge with CSWs) were compared and analysed. The results showed that the structural form and response of the main girder of a partial cable-stayed composite bridge are between those of a continuous rigid-frame composite bridge and a composite cable-stayed bridge. Compared with a concrete cable-stayed bridge of the same span, the self-weight of a partial cable-stayed composite bridge with CSWs is lighter, the main beam is lighter and the overall cost is less.